A mixed HWMA‐CUSUM mean chart with an application to manufacturing process. (15th September 2020) - Abid, Muhammad; Mei, Sun; Nazir, Hafiz Zafar; Riaz, Muhammad; Hussain, Shahid
Abstract: Memory‐type control charts play a significant role to identify slight changes in the parameters of the production process. In this article, we have proposed a new cumulative sum chart that utilizes the statistic of the homogeneously weighted moving average chart. The performance of the proposed chart is studied using Monte Carlo simulations. The proposed chart is compared with some existing charts under different run length profiles. The run length profile comparisons reveal that the proposed chart performs superior as compared to the existing control charts. A real‐life application using a manufacturing process dataset is also part of this study.